Sustainability of community-based interventions for people affected by dementia: a protocol for the SCI-Dem realist review - Morton, T; Atkinson, T; Brooker, D; Wong, G; Evans, S; Kennard, C (BMJ Publishing Group, 2019)
Introduction With numbers set to increase globally, finding ways to better support people with dementia and their families is a matter of growing concern. Community-based interventions can play a key role in supporting people with early to moderate stage dementia postdiagnosis, helping delay decline and hospitalisation. However, provision of such interventions is fragmented, with significant gaps and no reliable funding model, hence innovative groups and schemes catering for a genuine need can struggle long term and frequently fold. Methods and analysis This realist review aims to expand our understanding of how best to implement and facilitate community-based interventions to run sustainably, focusing on contextually relevant explanations. We will gather and synthesise literature using a realist approach designed to accommodate and account for the complexity of ‘real life’ programmes, as implemented under different conditions in different settings, aiming to draw transferable conclusions about their sustainability that explain how and why context can influence outcomes. Our review will iteratively progress through five steps: (1) locate existing theories; (2) search for evidence (using Academic Search, AMED, CINAHL, EMBASE, MEDLINE, ProQuest, PsycINFO, PubMed, Scopus and Social Care Online, between May and September 2019); (3) article selection; (4) extracting and organising data; (5) synthesising the evidence and drawing conclusions. Data analysis will use a realist logic to explain what works, for whom, in what circumstances, in what respects, how and why. A stakeholder group will provide guidance and feedback throughout. Ethics and dissemination Ethical approval was not required. Recommendations drawn from results are likely to be of interest to a range of stakeholders including those commissioning, planning, running, supporting or attending such interventions, as well as policymakers, healthcare professionals and researchers. We will draw on the expertise of our stakeholder group regarding tailoring dissemination to each audience using a variety of materials, formats and channels.